One More Locke in Kant: Kant’s “Epigenesis of Pure Reason” and Locke’s “Generatio Aequivoca” - Tomida, Yasuhiko (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2025)
Kant sees the acquisition of basic concepts from an embryological point of view and calls his theory of representations “a system of the epigenesis of pure reason.” According to this theory, not the pure concepts themselves but their “germs” or “predispositions” are inherent in the mind, and the concepts express themselves with the help of sensations qua “occasional causes.” In contrast, Kant calls Lockean empiricism “a sort of generatio aequivoca,” suggesting that it is “absurd.” In this article, I ﬁrst show that Locke’s position is not as different from Kant’s as Kant suggests. Then, I make it clear that Kant is a disguised Lockean empiricist and that his epigenesis is a Wittgensteinian “idle wheel.” The application condition (schema) for the concept of cause that Kant speciﬁes is nothing more than what Locke and Hume adduce; therefore, as far as the category of causality is concerned, Kant’s epigenetic theory does not have any real effect that would cause it surpass Locke’s. In addition, Kant’s assertion that experience does not teach necessity is based on the Humean phenomenalist perspective, and it diminishes the necessity of the pure concepts that Kant sees as indispensable to establishing “experience” of “nature.”